2020
DOI: 10.3390/biomedicines8110486
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Inhibits Glutamate Release and Prevents against Kainic Acid-Induced Excitotoxic Injury in Rats

Abstract: Silymarin, a polyphenoic flavonoid derived from the seeds of milk thistle (Silybum marianum), exhibits neuroprotective effects. In this study, we used a model of rat cerebrocortical synaptosomes to investigate whether silymarin affects the release of glutamate, an essential neurotransmitter involved in excitotoxicity. Its possible neuroprotective effect on a rat model of kainic acid (KA)-induced excitotoxicity was also investigated. In rat cortical synaptosomes, silymarin reduced glutamate release and calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 72 publications
5
46
0
Order By: Relevance
“…To date, no data documenting the effect of ISL on glutamate release was available. Several reports have indicated that natural products may effectively reduce the release of glutamate [20][21][22][23]. We examined whether ISL exhibited an effect on glutamate release in rat cerebrocortical nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no data documenting the effect of ISL on glutamate release was available. Several reports have indicated that natural products may effectively reduce the release of glutamate [20][21][22][23]. We examined whether ISL exhibited an effect on glutamate release in rat cerebrocortical nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reduced glutamatergic transmission through the inhibition of released glutamate has been proposed as a neuroprotective mechanism [17][18][19]. Studies have reported that several natural products with neuroprotective effects may reduce presynaptic glutamate release [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Fresh brain tissues from both the hippocampi were collected for synaptosomal preparation and Western blot analysis. The KA dose and administration schedule were chosen based on previous experiments [ 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Synaptosomes were prepared from male Sprague-Dawley rats as described previously [ 30 , 32 ]. Briefly, rats ( n = 3/group) were sacrificed through rapid decapitation, and the hippocampus was removed and homogenized in 0.32 M sucrose.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the glutamatergic system is a promising target for treatment of these diseases. Some studies have suggested that the inhibition of glutamate release by nerve terminals can help to prevent excitotoxic damage ( Wong et al ., 2015 ; Chang et al ., 2016 ; Lu et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%